Résumé du dialogue : Optimisation de la prestation de soins complets pour les personnes vivant avec le VIH au Canada - Waddell, K; Wilson, MG; Lavis, JN (My University, 2019)
A thematic summary of what was learned from the stakeholder dialogue on enhancing the delivery of comprehensive care for people living with HIV in Canada, about the problem (and its causes), elements of a potentially comprehensive approach for addressing it, key implementation considerations, and possible next steps.
Keywords: delivery; comprehensive care; Canada; HIV